Stink and the Midnight Zombie Walk - McDonald, Megan; Reynolds, Peter, 1961- (Somerville, Mass. : Candlewick Press, 2012)
Stink and his friends try to earn money to buy the latest book in the Nightmare on Zombie Street series and go to the book release party.
Keywords: Zombies -- Juvenile fiction; Books and reading -- Juvenile fiction; Money-making projects for children -- Juvenile fiction